Taking the first step: protocol for a cluster randomised implementation trial comparing strategies on access to exercise programmes for people with knee osteoarthritis - Jocelyn L Bowden; Kathryn Mills; Justine M Naylor; Joseph Descallar; Robert Boland; Margery Pardey (BMJ Open)
Introduction This cluster randomised implementation trial will assess the effect of two behavioural change interventions on the proportion of people with structural knee osteoarthritis (OA) referred and attending exercise-based professionals (physiotherapists and exercise physiologists). The interventions are designed to increase awareness of guidelines, benefits and access pathways for exercise therapy. We hypothesise either strategy will result in more people with knee OA being referred and attending physiotherapy/exercise physiology than current standard of care.Methods and analysis We will recruit 30 radiology clinics. 10 clinics will be randomly assigned to each trial arm with 1020 people with knee OA consecutively recruited (102 people per practice) into each arm. Intervention arm 1 is an educational reminder message targeted at primary care practitioners with a hyperlink to national guidelines regarding knee OA clinical management. It will be included in the reporting template of a plain knee X-ray. Intervention arm 2 is the reminder message and a patient-facing infographic explaining the benefits and access pathways for exercise. Both interventions will be delivered once, by the radiology clinics, when a person undergoes plain X-ray for non-traumatic knee pain/dysfunction. The primary outcome is referral to physiotherapist/exercise physiology. The secondary outcome is attendance to that appointment. Both outcomes are self-reported via an online survey administered 4 weeks after the X-ray. Additional survey questions explore facilitators and barriers to appointment attendance and acceptability of the interventions. A subsample of the intervention groups will be recruited for semistructured telephone-based interviews to further explore these latter outcomes.Ethics and dissemination The study protocol was approved by Macquarie University Human Research Ethics Committee (#520221190343842) and prospectively registered with the Australian New Zealand Clinical Trials Registry. The findings of the trial will be disseminated through peer-reviewed scientific journals and conferences. We will engage with Australian physician colleges and main-stream media to distribute findings.Trial registration number ACTRN12622001414707p.